Combined Vision and Hearing Difficulties Results in Higher Levels of Depression and Chronic Anxiety: Data From a Large Sample of Spanish Adults - Pardhan, Shahina; Smith, Lee; Bourne, Rupert; Davis, Adrian; Leveziel, Nicolas; Jacob, Louis; Koyanagi, Ai; López-Sánchez, Guillermo F. (Frontiers in Psychology, 2021)
Objective: Individually, vision and hearing impairments have been linked to higher levels of anxiety and depression. We investigated the effect of dual sensory impairment (difficulty seeing and hearing) in a large representative sample of Spanish adults. Methods: Data from a total of 23,089 adults (age range: 15-103 years, 45.9% men) from the Spanish National Health Survey 2017 were analysed. Self-reported difficulty of seeing and hearing (exposures), and depression and chronic anxiety (outcomes) were analysed. Multivariable logistic regression was assessed for difficulty with vision alone, hearing alone and with difficulty with both, adjusting for gender, age, marital status, living as a couple, education, smoking, alcohol consumption, BMI, physical activity, use of glasses/contact lenses and hearing aid. Results: Visual difficulty, hearing difficulty, and dual difficulties were all associated with significantly higher odds for depression (ORs 2.367, 2.098 and 3.852, respectively) and for chronic anxiety (ORs 1.983, 1.942 and 3.385, respectively). Dual sensory difficulty was associated with higher odds ratios for depression and anxiety when compared to either impairment alone. Conclusions: Dual sensory difficulty is associated with significantly higher odds of anxiety and depression when compared to either vision or hearing difficulty alone. Appropriate interventions are needed to address any reversible causes of vision and hearing as well as anxiety and depression in people in these specific groups.